2013
DOI: 10.1016/j.brainres.2013.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium level is an important factor influencing ion channel modulations by PLC-coupled metabotropic receptors in hippocampal neurons

Abstract: Abbreviations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The available evidence indicates that G-protein coupled receptors (GPCR) mediate the activation of phospholipase C-β (PLCβ) leading to the formation of inositol trisphosphate (InsP 3 ) and diacylglycerol (DAG) [ 34 ]. DAG directly activates classical types of PKCs, and IP3 activates intracellular Ca 2+ [ 35 ]. Therefore, we then examined the potential involvement of PLCβ in the transactivation of EGFR using the PLC inhibitor U73122 (20 μM).…”
Section: Resultsmentioning
confidence: 99%
“…The available evidence indicates that G-protein coupled receptors (GPCR) mediate the activation of phospholipase C-β (PLCβ) leading to the formation of inositol trisphosphate (InsP 3 ) and diacylglycerol (DAG) [ 34 ]. DAG directly activates classical types of PKCs, and IP3 activates intracellular Ca 2+ [ 35 ]. Therefore, we then examined the potential involvement of PLCβ in the transactivation of EGFR using the PLC inhibitor U73122 (20 μM).…”
Section: Resultsmentioning
confidence: 99%
“…ER is the predominant source of Ca 2+ in the cytoplasm; thus, the fluxes from mitochondria and other acidic organelles have not been considered (Samtleben et al, 2015). Both PLCβ and PLCδ pathways play a role in modulating the Ca 2+ activity in the cells (de Pittà et al, 2009; Matrosov et al, 2019; Sugawara et al, 2013). The Ca 2+ concentration in the ECF stays approximately constant. The neurons were assumed to be maintaining physiological conditions (not pathological).…”
Section: Methodsmentioning
confidence: 99%
“…3. Both PLCβ and PLCδ pathways play a role in modulating the Ca 2+ activity in the cells (de Pittà et al, 2009;Matrosov et al, 2019;Sugawara et al, 2013).…”
Section: Model Descriptionmentioning
confidence: 99%
“…This muscarinic current response was inhibited by the phospholipase C (PLC) inhibitor U73122, but not its inactive analogue U73343, indicating the involvement of PLC-coupled types of muscarinic receptors including M 1 and M 3 subtypes (Sugawara et al, 2013). In the present study, using this muscarinic current response we assessed muscarinic agonist and antagonist activities of clozapine and NDMC in intact hippocampal excitatory and inhibitory neurons.…”
Section: Introductionmentioning
confidence: 90%
“…We previously reported that in rat cultured hippocampal neurons the activation of muscarinic receptors by applying the muscarinic agonist oxotremorine M (oxo-M) decreased the steady-state outward current at -40 mV, which was attributed to inhibition of K + channels sensitive to the M-current blocker XE991 (Sugawara et al, 2013). This muscarinic current response was inhibited by the phospholipase C (PLC) inhibitor U73122, but not its inactive analogue U73343, indicating the involvement of PLC-coupled types of muscarinic receptors including M 1 and M 3 subtypes (Sugawara et al, 2013).…”
Section: Introductionmentioning
confidence: 99%